Germination Changes The Chemical Composition and Improves Antioxidant Activity of Indonesian Local Brown Rice var Mentikwangi: Germinasi Merubah Komposisi Kimia dan Meningkatkan Aktivitas Antioksidan pada Beras Pecah Kulit Lokal var Mentikwangi - Saputra, Wahyu Dwi; Saputra, Adrian Dwi; Triwitono, Priyanto (Universitas Slamet Riyadi Surakarta, 2024)
Previously, germination was reported in many studies that could improve the nutritional status and bioactive compounds in brown rice. However, the change of those functional properties was randomly different in diverse varieties. This study aimed to evaluate the change in chemical composition and functional properties of germinated brown rice from the Mentikwangi variety, one of the local paddy rice in Indonesia. Brown rice was germinated using the soaked and aeration method for 48 h. After that, the proximate compositions were analyzed including the change of total phenolic compounds and radical scavenging activity. We observed that germination in Mentikwangi brown rice significantly increased the crude protein content, but reduced the lipid and total carbohydrate contents. Moreover, the antioxidant activity was improved in germinated Mentikwangi brown rice sample due to the improvement of total phenolic compounds. These results affirm the previous studies which concluded that germination attenuated the functional properties of brown rice, so that has the potential to be developed as a future functional food.